Exploring the Voices of Indonesian Non-Native English-Speaking Teachers Teaching Abroad - Ancila Putri Perwitasari; Hanna Sundari (Deiksis, 2022)
Being non-native English-speaking teachers (non-NESTs) comes with challenges and opportunities. The purpose of this research was to explore the teaching experience and practices of Indonesian teachers who teach English and how they see themselves as NNESTs teaching in northeastern Thailand. Guided by qualitative approach of interview research inquiry by Kvale (2007), six Indonesian teachers who teach English in northeastern Thailand were invited and took part in two phases of interview sessions. The findings show that to teach English in Thailand, Indonesian teachers were driven by various internal motivation including expanding teaching experience, receiving recognition, and getting higher salary. During their job assignment as English teachers at primary/secondary in several districts in northeastern region, they have encountered bittersweet life and teaching experiences. Language barrier is one of the prominent problems since Indonesian teachers and Thai students speak different languages. Moreover, unavailability of teaching sources and student factors have become the next challenge to cope. Application of various teaching strategies and adjustment to student levels can be a realistic solution to maintain professional teaching service. Furthermore, they also admitted that Thai students and other Thai teachers are welcomed, and they felt positive acceptance. They also mentioned that their presence as Indonesian non-NESTs teaching English in Thailand indicates that Indonesian teachers have international qualification to be English teachers at international level.